G05 High penetrance and frequent severe psychiatric manifestations in patients with 36–38 cag HTT repeats. (September 2018) - Marchionni, Enrica; Monin, Marie-Lorraine; Sayah, Sabrina; Brice, Alexis; Charles, Perrine; Durr, Alexandra
Abstract : Background: HTT alleles with a CAG repeat length of 36–38 are rare and known to be associated with reduced penetrance of Huntington disease, later age at onset and milder evolution. Aims: Report the clinical presentation of patients with an intermediate CAG repeat size of 36–38 CAG. Methods/techniques: Twenty–eight patients (18 women and 10 men) have been seen in the genetic department at the Pitié-Salpêtrière University Hospital. Familial history, parental inheritance, presence of symptoms (psychiatric and/or cognitive and/or motors) and age of onset were collected. Results/outcome: All but three patients had a familial history of Huntington disease, 17 maternally inherited, 7 paternally inherited. The mean age at first contact was 55.6±12.7 years [24–90]. Sixty four percent (18/28) of individuals with intermediate alleles presented clinical signs. The others (10/28) were not clinically affected at a mean age of 50.1±20.8 years [24–90]. Mean age at onset was 52.3±8.4 years [40–66]. At first examination, there were motor signs in most (83%, 15/18) patients, including chorea and dystonia. Interestingly, 72% (13/18) presented severe psychiatric symptoms such as depression, suicide attempts, aggressiveness, 23% (3/13) requiring hospitalization. Even more, 78% (14/18) presented cognitive symptoms in particular dysexecutive and attention impairments. This is in contrast to the milder phenotype expected with intermediate allele sizes. Conclusions: The major finding was the unexpected proportion and high severity of symptoms among patients carrying small and intermediate alleles in the HTT gene (36–38). This should be taken into account in genetic counselling.